THE MODERATING EFFECT OF ENVIRONMENTAL AWARENESS ON WILLINGNESS TO PAY FOR THE BODY SHOP PRODUCTS - Naniek Utami Handayani; M. Mujiya Ulkhaq; Maulida Asri (Universitas Sebelas Maret (UNS), 2026)
Single-use plastic consumption was so high that it led to a buildup of plastic waste, threatening the sustainability of ecosystems and marine life. Much of this plastic waste originated from environmentally unfriendly products, which had become an increasingly pressing social issue. This study investigated the impact of green product attributes, perceived price, and environmental awareness on consumers' purchase intentions for green products. Data were collected through a survey of 250 randomly selected respondents and analysed using descriptive statistics, validity and reliability tests, and Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess both measurement and structural relationships. Validity tests were conducted using product-moment correlation analysis, and reliability was measured using Cronbach's alpha coefficient. Hypothesis testing was carried out with the help of PLS-SEM software. The results showed that Attitude Toward Green Brand and Price & Value Perception positively and significantly influenced Green Purchase Intention, with regression coefficients of 0.232 and 0.198, respectively. However, environmental awareness did not significantly influence GPI, with a p-value coefficient of -0.052. This research provided important insights for developing green product marketing strategies, emphasising the importance of strengthening product attributes and perceived value to increase consumer purchase intentions. Theoretically, the findings extended the understanding of consumer behaviour in green marketing by confirming that perceived product value mediated the relationship between environmental concern and purchase intention, thereby enriching existing models of sustainable consumption.